Envelope for a letter from Miss "C. M. Sedgwick, authoress" in Lennox, Mass., to A. W. Thayer in New York, dated 7 Jul (year unknown). - Thayer, Alexander Wheelock, 1817-1897:::::::::::::::; Sedgwick, Catharine Marie, 1789-1867::::::::::::::: (2022)
Envelope for a letter from Miss "C. M. Sedgwick, authoress" (possibly Catherine Marie Sedgwick) in Lennox, Mass., to A. W. Thayer, addressed to the Tribune Office in New York, dated 7 Jul (year unknown); lacks the enclosed letter.